Spectral triples for higher-rank graph $C^*$-algebras - Farsi, Carla; Gillaspy, Elizabeth; Julien, Antoine; Kang, Sooran; Packer, Judith (MATHEMATICA SCANDINAVICA, 2020)
In this note, we present a new way to associate a spectral triple to the noncommutative $C^*$-algebra $C^*(Λ )$ of a strongly connected finite higher-rank graph Λ. Our spectral triple builds on an approach used by Consani and Marcolli to construct spectral triples for Cuntz-Krieger algebras. We prove that our spectral triples are intimately connected to the wavelet decomposition of the infinite path space of Λ which was introduced by Farsi, Gillaspy, Kang, and Packer in 2015. In particular, we prove that the wavelet decomposition of Farsi et al. describes the eigenspaces of the Dirac operator of our spectral triple. The paper concludes by discussing other properties of the spectral triple, namely, θ-summability and Brownian motion.